Relationships between antibiotic exposure and asthma in adults in the United States: results of the National Health and Nutrition Examination Survey between 1999 and 2018 - Li, Shaoli; Chen, Feilong; Huang, Chunlei; Huang, Guimin; Cheng, Yijing; Li, Tao; Hou, Dongqing; Liu, Wenqian; Xu, Tao; Liu, Junting (Frontiers in Public Health, 2023)
Objectives: To investigate the relationship between antibiotic exposure and asthma in adults in the United States. Methods: A cross-sectional survey of a nationally representative sample was performed using data from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2018 in participants aged ≥20 years. Antibiotic exposure was defined as the utilization of antibiotics within the past 30 days, categorized based on the Multum Lexicon Plus therapeutic classification system. All participants with a history of asthma and those who had an asthma attack or wheezing symptoms in the past year were studied. Results: A total of 51,124 participants were analyzed. The risk of asthma was found to be 2.557 (95% CI: 1.811, 3.612), 1.547 (95% CI: 1.190, 2.011) and 2.053 (95% CI: 1.344, 3.137) times greater in participants who had used macrolide derivatives, penicillin and quinolones in the past 30 days, respectively, compared with those not using antibiotics. After adjusting for demographic covariates and asthma-related factors, only macrolides derivatives were significantly associated with asthma in the 20 to 40 and 40 to 60 age groups. For individuals over 60 years old, quinolones were significantly associated with asthma. The effect of different types of antibiotic with asthma varied in male and female populations. Moreover, higher socioeconomic status, greater BMI, younger age, smoking habits, history of infection, chronic bronchitis, emphysema, and family history of asthma were all identified as risk factors for asthma. Conclusions: Our study indicated that three types of antibiotics were significantly association with asthma in different subgroups of the population. Therefore, the use of antibiotics should be more strictly regulated.